Computer teachers' attitudes towards using Madrasati platform in teaching in Al-Makhwah Governorate - Alessi, Muteb Abduallh Muteb (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the attitudes of Saudi male and female computer teachers towards the use of Madrasati platform in teaching in Al-Makhwah Governorate. The descriptive approach was used to achieve the objectives in this research.  Also, a questionnaire was designed as a tool for data collection. The results indicated that the attitudes of male and female computer teachers towards using Madrasati platform in teaching in Al-Makhwah Governorate are positive, with a mean of (3.84), with a percentage of (76.8%). The results showed that there is no significant effect of gender, stage or experience on teachers' attitude. In light of these results, the study recommended expanding the implementation of training courses, the need to continuously develop Madrasati platform, and the need to involve male and female teachers in developing Madrasati platform.
Keywords: computer and information technology curricula; trends; computer teachers; Madrasati platform